2005
DOI: 10.1097/00001199-200501000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and Ongoing Support After Pediatric TBI

Abstract: This article summarizes major developments of the past 20 years in both acute and chronic management of children with traumatic brain injury. The article begins with brief summaries of developments in acute and rehabilitative medical management and physical rehabilitation. Because long-term cognitive, behavioral, academic, and family issues tend to be dominant after pediatric TBI, more attention is given to these topics. The article ends with a list of general themes that have been identified as critical in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 41 publications
1
117
0
3
Order By: Relevance
“…However, selfefficacy alone is insufficient to effectively manage the complex learning and behavioral needs of students with TBI. Educators need to be trained to use methods that have been validated with students with TBI and to modify strategies validated with students with other disabilities (Dettmer, Ettel, Glang, & McAvoy, 2014;Glang, Todis, Sublette, Eagan-Brown, & Vaccaro, 2010;Ylvisaker et al, 2005;Ylvisaker et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…However, selfefficacy alone is insufficient to effectively manage the complex learning and behavioral needs of students with TBI. Educators need to be trained to use methods that have been validated with students with TBI and to modify strategies validated with students with other disabilities (Dettmer, Ettel, Glang, & McAvoy, 2014;Glang, Todis, Sublette, Eagan-Brown, & Vaccaro, 2010;Ylvisaker et al, 2005;Ylvisaker et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…For long-term planning to be secured the schools, and in some cases, the social services, have to be informed both of the present deficits of the child concerned and of how the everyday consequences may evolve in the coming years (Savage et al 2005). Ylvisaker et al (2005) pointed out that studies have shown that the profile of cognitive and behavioural abilities after injury at a young age often worsens over the years after the injury, instead of improving as might be expected by parents and teachers. Ylvisaker et al (2005) outlined detailed descriptions of research-based instructional strategies associated with common CTBI impairments, such as organizational impairment, inefficient learning, decreased speed of processing and fluctuating attention.…”
Section: The Child´s Coping With Persisting Deficitsmentioning
confidence: 99%
“…Ylvisaker et al (2005) pointed out that studies have shown that the profile of cognitive and behavioural abilities after injury at a young age often worsens over the years after the injury, instead of improving as might be expected by parents and teachers. Ylvisaker et al (2005) outlined detailed descriptions of research-based instructional strategies associated with common CTBI impairments, such as organizational impairment, inefficient learning, decreased speed of processing and fluctuating attention. However, many children with special educational needs attributable to TBI are not identified and their needs may not be connected to the injury .…”
Section: The Child´s Coping With Persisting Deficitsmentioning
confidence: 99%
“…Involving them in the process of rehabilitation fosters a sense of control and contributes towards eliminating the negative influence of powerlessness. Studies have shown that, irrespective of their educational levels, parents are capable of conducting neurodevelopmental exercises at home with their child, with the prior training and guidance from a professional team [1,3,4].…”
Section: Editorialmentioning
confidence: 99%